Report of the 5th European expert meeting on rotavirus vaccination (EEROVAC) - Marieke L. A. de Hoog; Timo Vesikari; Carlo Giaquinto; Hans-Iko Huppertz; Federico Martinon-Torres; Patricia Bruijning-Verhagen (Taylor & Francis Group, 2018)
The Fifth European Expert Meeting on Rotavirus Vaccination was convened in Utrecht, The Netherlands, in March 2017. The 2-day meeting included invited lectures as well as original oral and poster presentations and brought together experts from 21 countries. Summary findings of the meeting include: Rotavirus vaccination programmes in Europe have resulted in reductions of 60-90% in rotavirus outpatient visits and hospitalizations. Long term trends indicate this impact is sustained over the years. Herd effects, protecting unvaccinated children and neonates too young to be vaccinated have been observed in many European countries. Early evidence now also suggests that rotavirus vaccination may be instrumental in the prevention of celiac disease. Special attention should be given to preterm infants, who may age out of the vaccination window before hospital discharge and to HIV infected children who are at increased risk of severe rotavirus AGE. There is a small but increased risk of IS following rotavirus vaccination and parents should therefore be informed about possible signs and symptoms of IS. New insights in rotavirus genetic susceptibility and interactions with microbiome may open opportunities for interventions to improve protection by vaccination, in particular in LMIC. The development of several novel rotavirus vaccines discussed at the meeting is also promising in this respect.